Tutor Sebaya untuk Meningkatkan Hasil Belajar Menghitung Pada Siswa SD - Masyruroh, Luluk (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study is to prove that learning outcomes to calculate the area of a flat shape can be increased through the use of Peer Tutor learning methods for second grade students of SDN 2 Kismantoro in the 2021/2022 academic year. This research was conducted with a total of 21 students. This research was carried out for 2 cycles where each cycle was carried out in 2 meetings. The design of the research implementation was carried out through four stages, namely: planning, implementing actions, observing, and reflecting. The results of the observations were discussed with colleagues to find out the improvements that occurred during the research. The results obtained at the end of the second cycle in the form of an increase in the achievement of learning process indicators, namely activeness 76.19.%, enthusiasm 85.71%, and independence 85.71%. Students who have high/very high motivation are 85.71%. The average student learning outcomes reached 76.67 with classical completeness reaching 90.48%. From the results of these studies, it can be concluded that the motivation and learning outcomes to calculate the area of polygons can be increased through the Peer Tutor learning method.